Mission-centric learning strategy TBLC in collecting geographical material for fifth grade literary students - Dalah, Khadeeja Hasan; Abdullah, Ismael Hasan (Edelweiss Applied Science and Technology, 2024)
This research aims to learn (the impact of the mission-based learning strategy TBLC in the collection of geographical material for literary fifth graders) To achieve the research objective, the researcher adopted a partially tuned experimental design that is the design of the experimental group and a control group with a dimensional test. The research community consisted of the daytime middle and high schools of the General Directorate of First Karakh Education, and was selected as a preparatory (Anfal) for girls in a simple random way to be the research sample, and the sample consisted of two literary fifth grade divisions, representing a division (a) Pilot Group and Division (b) Control Group, search sample reached 60 students, 30 students in the pilot group and 30 students in the control group, while for statistical means the researcher used (Box Kai, T test for two independent samples, Pearson's correlation coefficient for the vertebrae, the results yielded the following: Statistically significant differences exist between the average achievement of female students of the pilot group who have studied according to the strategy (TBL task-based learning) and the average scores of female students of the control group who have studied according to the traditional method, and for the benefit of the pilot group.